An organic molecular compound for in situ identification of mitochondrial G-quadruplexes in live cells. Issue 3 (23rd December 2021) - Guo, Xiaomeng; Chen, Hongbo; Liu, Yan; Yang, Dawei; Li, Qian; Du, Hongyan; Liu, Meirong; Tang, Yalin; Sun, Hongxia
Abstract : An organic compound can highly target the mitochondria of living cells and light up the G-quadruplex structure in the mitochondria with high specificity. Abstract : Emerging studies have shown that mitochondrial G-quadruplex plays a critical role in regulating mitochondrial gene replication and transcription, which makes it a promising target for the diagnosis and treatment of cancer or other major diseases. Molecular compounds that can highly target the mitochondrial G-quadruplexes in live cells are essential for further revealing the function and mechanism of these G-quadruplexes. Here, we have developed an organic molecular compound that can highly target the mitochondria of living cells by virtue of the membrane potential mechanism. Then it shows high selectivity to the G-quadruplex structure in the mitochondria, and its fluorescence overlaps well with that of the BG4 antibody. Moreover, the compound has extremely low cytotoxicity and does not interfere with the natural state of G-quadruplex structure. With these good properties, this compound will have great potential in mitochondrial G-quadruplex tracking research or targeted drug screening.